2020
DOI: 10.1038/s41467-020-19850-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantized thermoelectric Hall effect induces giant power factor in a topological semimetal

Abstract: Thermoelectrics are promising by directly generating electricity from waste heat. However, (sub-)room-temperature thermoelectrics have been a long-standing challenge due to vanishing electronic entropy at low temperatures. Topological materials offer a new avenue for energy harvesting applications. Recent theories predicted that topological semimetals at the quantum limit can lead to a large, non-saturating thermopower and a quantized thermoelectric Hall conductivity approaching a universal value. Here, we exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…This has the advantage that the equations presented are quite general, and thus our theoretical predictions for the transport coefficients can be compared with specific experimental measurements by choosing the appropriate material-dependent parameters. For instance, choosing the dimensions of the slab as W ∼ L ∼ 50 nm and the radius of the cylindrical strip as a ∼ 15 nm, we obtain an electrical resistivity ρ ∼ 2.15 × 10 −4 Ωm which is within the range reported in [37] (ρ ∼ 2 × 10 −2 Ωm for Bi and ρ ∼ 10 −5 Ωm for TaP). On the other hand, for the case of the thermal conductivity, using the Fermi velocity v F ∼ 1.5 × 10 6 m/s for the material Cd 3 As 2 [34], and the same values for a, L, and W as before, we found a value of κ ∼ 6.6 W/mK which is of the same order of magnitude to those reported in [36] (∼ 3 W/mK for Pb 1−x Sn x Se) and in [37] (∼ 5 − 25 W/mK for TaP).…”
Section: Discussionsupporting
confidence: 74%
“…This has the advantage that the equations presented are quite general, and thus our theoretical predictions for the transport coefficients can be compared with specific experimental measurements by choosing the appropriate material-dependent parameters. For instance, choosing the dimensions of the slab as W ∼ L ∼ 50 nm and the radius of the cylindrical strip as a ∼ 15 nm, we obtain an electrical resistivity ρ ∼ 2.15 × 10 −4 Ωm which is within the range reported in [37] (ρ ∼ 2 × 10 −2 Ωm for Bi and ρ ∼ 10 −5 Ωm for TaP). On the other hand, for the case of the thermal conductivity, using the Fermi velocity v F ∼ 1.5 × 10 6 m/s for the material Cd 3 As 2 [34], and the same values for a, L, and W as before, we found a value of κ ∼ 6.6 W/mK which is of the same order of magnitude to those reported in [36] (∼ 3 W/mK for Pb 1−x Sn x Se) and in [37] (∼ 5 − 25 W/mK for TaP).…”
Section: Discussionsupporting
confidence: 74%
“…Recent theoretical works suggested the possibility of record-high thermoelectric conversion efficiency in semiconductors and semimetals under a quantizing magnetic field [3,4], where the thermoelectric response is directly related to entropy [5][6][7][8]. Based on this relation, it is found that the thermopower of three-dimensional (3D) Dirac and Weyl materials in the quantum limit increases unboundedly with magnetic field [3,[9][10][11][12]. Very recently, it is shown that two-dimensional (2D) quantum Hall systems can reach a thermoelectric figure of merit on the order of unity down to low temperature (T ), as a consequence of the thermal entropy from the massive Landau level (LL) degeneracy [4].…”
mentioning
confidence: 99%
“…In fact, the advantageous opportunity of concurrently applying external magnetic and electric fields during the measurement, which is not applicable with the aforementioned techniques, in addition to possibly enhanced resolution capabilities positions inelastic neutron scattering as a possible enabler of further discoveries in the realm of TNMs. The direct probing of electronic bands with neutron scattering also differs from probing topology with its lattice degrees of freedom [58,74,75].…”
Section: Discussionmentioning
confidence: 99%